2018
DOI: 10.1136/bmjdrc-2017-000503
|View full text |Cite
|
Sign up to set email alerts
|

Real-world crude incidence of hypoglycemia in adults with diabetes: Results of the InHypo-DM Study, Canada

Abstract: ObjectiveVery few real-world studies have been conducted to assess the incidence of diabetes-related hypoglycemia. Moreover, there is a paucity of studies that have investigated hypoglycemia among people taking secretagogues as a monotherapy or in combination with insulin. Accordingly, our research team developed and validated the InHypo-DM Person with Diabetes Mellitus Questionnaire (InHypo-DMPQ) with the aim of capturing the real-world incidence of self-reported, symptomatic hypoglycemia. The questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 46 publications
3
84
2
6
Order By: Relevance
“…Previous studies with CGM showed that hypoglycemia occurred more frequently during the night than during the daytime in insulin-treated patients with type 1 or type 2 diabetes 18,19 . In contrast, daytime hypoglycemic events were more frequent than nocturnal hypoglycemic events in a study based on self-reporting of such events 20 . In the present study, we found that the duration of nocturnal hypoglycemia was longer than that of daytime hypoglycemia, and became longer as the HbA 1c level decreased.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies with CGM showed that hypoglycemia occurred more frequently during the night than during the daytime in insulin-treated patients with type 1 or type 2 diabetes 18,19 . In contrast, daytime hypoglycemic events were more frequent than nocturnal hypoglycemic events in a study based on self-reporting of such events 20 . In the present study, we found that the duration of nocturnal hypoglycemia was longer than that of daytime hypoglycemia, and became longer as the HbA 1c level decreased.…”
Section: Discussionmentioning
confidence: 84%
“…There was a numerically greater rate of severe hypoglycaemia in older individuals compared with younger individuals (RR, 1.38) in the current trial, although the trend was not statistically significant. Severe hypoglycaemia is generally much more common in real‐world populations than in randomized clinical trials . In addition, continuous glucose monitoring has demonstrated that many episodes are unrecognized and under‐reported .…”
Section: Discussionmentioning
confidence: 99%
“…Severe hypoglycaemia is generally much more common in real-world populations than in randomized clinical trials. 4,5,32 In addition, continuous glucose monitoring has demonstrated that many episodes are unrecognized and under-reported. 33 Furthermore, it has been estimated that only 5% of self-reported severe hypoglycaemia events among individuals with diabetes who are underging pharmacological treatment are captured by traditional healthcare utilization-based surveillance systems, suggesting a substantial underestimate of the true burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations